PENGEMBANGAN HOMESTAY BERBASIS PENDIDIKAN SEBAGAI PRODUK WISATA UNTUK MEMBANGUN MASYARAKAT BERKELANJUTAN PADA DESA TERPENCIL DI SULAWESI SELATAN - Rosfiah Arsal; Muhammad Basri (Journal Publicuho, 2023)
This research aims to determine the development of education-based homestays as a tourism product, a tourism approach that is considered to be able to achieve progress in sustainable community development programs in remote villages in South Sulawesi. The method used is based on a literature review of various disciplines including cultural tourism, community-based tourism, sustainable tourism, nature conservation and environmental geography. Data searches were carried out using online databases, tourism programs, Homestay Programs and data sourced from Science Direct journals, Google Scholar and so on. Research findings show that many direct and indirect benefits are created by the development of education-based homestays. They not only help in assisting in the education and skills education of the community but more broadly, namely contributing to improving the welfare of local communities and gender equality and lifting entire families out of poverty while maintaining decision-making in the community.